Effectiveness Development Learning Guidebook Strengthening Pancasila Values for Children Aged 5-6 Years - Anik Lestariningrum; Etty Andyastuti; Nur Lailiyah; Intan Prastihastari Wijaya; Yatmin; Dwi Yogi Karisma (PT Inovasi Pratama Internasional, 2023)
Objective study This is to produce a book that guides learning as strengthening children's Pancasila values at an early age of 5–6 years. It is valid, practical, and effective. The method of research used is research and development with a 4D development model consisting of stages: define, design, develop, and disseminate. Findings study This that is study This succeeds in developing a book guide for learning customized with material curriculum independent of strengthening children's Pancasila values phase foundation. Based on the difference in results between the pretest and posttest, it can be concluded that the book guide developed learning already effective. Implications from the study This, i.e., order book guide, can be developed on other topics done in training towards teachers more widely about how to use book guides to learn based on Pancasila values, interesting interest, and participant education to learn and give positive marks in support of strengthening the profile of Pancasila students in the implementation of curriculum at the independent preschool level.